2005
DOI: 10.1038/nature03827
|View full text |Cite
|
Sign up to set email alerts
|

Trace-element fractionation in Hadean mantle generated by melt segregation from a magma ocean

Abstract: Calculations of the energetics of terrestrial accretion indicate that the Earth was extensively molten in its early history. Examination of early Archaean rocks from West Greenland (3.6-3.8 Gyr old) using short-lived 146Sm-142Nd chronometry indicates that an episode of mantle differentiation took place close to the end of accretion (4.46 +/- 0.11 Gyr ago). This has produced a chemically depleted mantle with an Sm/Nd ratio higher than the chondritic value. In contrast, application of 176Lu-176Hf systematics to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 29 publications
4
84
0
Order By: Relevance
“…4). However, one paradox has been that early Archean (3.96 Gy) rocks from Isua, Greenland already show positive deviations in 143 Nd/ 144 Nd ( 143 Nd is the decay product of 147 Sm, a longer-lived isotope of Sm) relative to chondrite but little to no concomitant anomaly in 176 Hf/ 177 Hf (Bennett et al, 1993;Bowring and Housh, 1995;Vervoort and Blichert-Toft, 1999;Bennett, 2003;Bizzarro et al, 2003;Caro et al, 2005). This requires that the Hadean upper mantle (blue ovals in Fig.…”
Section: Decoupling Of Sm/nd and Lu/hfmentioning
confidence: 91%
See 2 more Smart Citations
“…4). However, one paradox has been that early Archean (3.96 Gy) rocks from Isua, Greenland already show positive deviations in 143 Nd/ 144 Nd ( 143 Nd is the decay product of 147 Sm, a longer-lived isotope of Sm) relative to chondrite but little to no concomitant anomaly in 176 Hf/ 177 Hf (Bennett et al, 1993;Bowring and Housh, 1995;Vervoort and Blichert-Toft, 1999;Bennett, 2003;Bizzarro et al, 2003;Caro et al, 2005). This requires that the Hadean upper mantle (blue ovals in Fig.…”
Section: Decoupling Of Sm/nd and Lu/hfmentioning
confidence: 91%
“…Sequestering a Hadean residual liquid with high Lu/Hf would drive the remaining part of the mantle towards low Lu/Hf at a given Sm/Nd. It is clear that both low (this study) and high pressure (Caro et al, 2005) fractionation processes in a magma ocean could act together or separately to decouple Hf and Nd isotopes during Earth's early history.…”
Section: Decoupling Of Sm/nd and Lu/hfmentioning
confidence: 96%
See 1 more Smart Citation
“…Bennett et al, 2007;Boyet et al, 2003;Caro et al, 2003;Debaille et al, 2013;O'Neil et al, 2008;Rizo et al, 2011;Roth et al, 2013). Investigating how early-formed reservoirs with discrete 146 Sm/ 144 Nd were dispersed and homogenised within the Earth over geological time-scales yields important information on the physical structure of the early terrestrial mantle (Bennett et al, 2007;Caro et al, 2003Caro et al, , 2005Debaille et al, 2013;Harper and Jacobsen, 1992;Rizo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms have been proposed for the early partial differentiation of the Earth's mantle, including fractional crystallization of a regular magma ocean (Solomatov and Stevenson 1993;Solomatov 2007), crystallization of a basal magma ocean (Labrosse et al 2007), which also explains the ultra-low seismic velocity zones (ULVZ) observed locally at the bottom of the mantle (Garnero and Helmberger 1995;Williams and Garnero 1996), 'upside-down' differentiation (Lee et al 2010), which consists of the formation, crystallization, and sinking of dense liquids in the upper mantle during the Earth's first billion year, and the recycling of a primitive crust (Tolstikhin et al 2006), which is supported by geochemical data (Boyet and Carlson 2006;Caro et al 2003Caro et al , 2004 and numerical models of convection (van Thienen et al 2004(van Thienen et al , 2005. Alternatively, models of mantle composition based on E-chondrite predict that the composition in main oxides of the lower mantle is different from that of the upper mantle (Javoy et al 2010).…”
Section: Early Differentiated Materials Versus Recycled Morbmentioning
confidence: 87%